Current Understanding of Circular RNAs in Systemic Lupus Erythematosus - Liu, Hongjiang; Zou, Yundong; Chen, Chen; Tang, Yundi; Guo, Jianping (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is a common and potentially fatal autoimmune disease that affects multiple organs. To date, its etiology and pathogenesis remains elusive. Circular RNAs (circRNAs) are a novel class of endogenous non-coding RNAs with covalently closed loop structure. Growing evidence has demonstrated that circRNAs may play an essential role in regulation of gene expression and transcription by acting as microRNA (miRNA) sponges, impacting cell survival and proliferation by interacting with RNA binding proteins (RBPs), and strengthening mRNA stability by forming RNA-protein complexes duplex structures. The expression patterns of circRNAs exhibit tissue-specific and pathogenesis-related manner. CircRNAs have implicated in the development of multiple autoimmune diseases, including SLE. In this review, we summarize the characteristics, biogenesis, and potential functions of circRNAs, its impact on immune responses and highlight current understanding of circRNAs in the pathogenesis of SLE.